Ekstraksi Dan Karakterisasi Glukomanan dari Umbi Porang (Amorphophallus Muelleri Blume) dari Perum Perhutani - Amyranti, Mutia; Nurlatifah, Ismi; Chairunisa, Chairunisa (JURNAL ILMIAH FAKULTAS TEKNIK, 2024)
Porang tubers (Amorphophallus muellei Blume) belong to the Amorphallus genus. Porang tubers contain relatively high levels of glucomannan. Glucomannan is widely used in many industrial fields such as the food, beverage, cosmetics and medicine industries. This research was conducted to determine the sodium metabisulfite ratio levels and maceration time in the process of making porang tuber flour so that optimal porang flour is produced. Varying concentrations of sodium metabisulfite used were 0.2%, 2% and 5% with a soaking time of 1-3 hours and extraction with 60% ethanol. The highest level of glucomannan produced was when using 5% sodium metabisulfite with a 3 hour soaking process with a value of 64.575%.